The The Influence of School Well-Being on Learning Achievement of Full Day School of Elementary Students - Lebdaningrum, Anissa Nur; Zainuddin, Almuntaqo (Lectura : Jurnal Pendidikan, 2024)
The objective of this study is to investigate the correlation between school well-being and academic performance among full-day students enrolled at MI Muhammadiyah PK Wirogunan Kartasura. This is a descriptive-quantitative study employing an explanatory methodology. The study sample comprised 127 upper-class students enrolled at MI Muhammadiyah PK Wirogunan Kartasura during the academic year 2022–2023. The research employed a total sampling technique to select the sample, resulting in 127 samples utilised for the study. This research makes use of documentation, questionnaires, and observation as data collection methods. Simultaneously, a questionnaire comprising 25 items was employed as the data collection instrument in this study. This study employs a variety of data analysis techniques, including tests of research instruments' validity and reliability, tests of classical assumptions, and hypothesis testing via simple linear regression analysis. The findings of this research indicated that student learning achievement at MI Muhammadiyah PK Wirogunan Kartasura was significantly impacted by school well-being. The t-count value (3.7788) exceeded the critical t-value (1.657) from the t-table, and the p-value (0.000) was less than 0.05. Furthermore, according to the findings of the study, the indicator of belonging in school well-being has the highest mean value.